Determine key drivers of employee engagement among nurses in a healthcare sector: a case of KPJ Damansara Specialist Hospital / Nurfitryannie Asik - Asik, Nurfitryannie (Faculty of Business and Management, 2020)
Employee engagement is becoming a major concern to employers in the era of globalization particularly in the healthcare industry. In the Malaysian context the healthcare industry is becoming more attractive and it is preferred by patients all over the world. Thus, employee engagement can be described as employee that show full commitment towards their job; physically and emotionally in order to achieve the organizational goal. This conducted because study on engagement among nursing has not yet been synthesized, thus there is insufficient foundation of knowledge to regulate practice and there is urgency for further research. The purpose of this research is to investigate key drivers of employee engagement among nurses in a healthcare sector specifically in KPJ Damansara Specialist Hospital. This study used convenience sampling techniques and online questionnaire as an instrument to collect data. Respondent feedback is 72% out of 305 nurses whereby those data then evaluated by using SPSS Version 22 Software. The result from Multiple Regression analysis indicates that two variables of employee engagement; work life balance and leadership have positive and significant relationship with employee engagement while communication is not significant. Lastly, work life balance found to be the most influential variables towards employee engagement among nurses in KPJ Damansara Specialist Hospital.